The house on vesper sands ebook - O'Donnell, Paraic (2021)
An Oprah Daily and CrimeReads Best Historical Novel of 2021 Named a Library Reads Pick, Apple Books' Best Book, Amazon Fiction & Literature's "Best of the Month," and a Powell's Pick The Millions' Top Ten Book of the Month "Funny, eerie, tender, haunting and unsettling, smokily atmospheric, and fantastically enjoyable." —Helen Macdonald, author of Vesper Flights London, 1893: high up in a house on a dark, snowy night, a lone seamstress stands by a window. So begins the swirling, serpentine world of Paraic O'Donnell's Victorian-inspired mystery, the story of a city cloaked in shadow, but burning with questions: why does the seamstress jump from the window? Why is a cryptic message stitched into her skin? And how is she connected to a rash of missing girls, all of whom seem to have disappeared under similar circumstances? On the case is Inspector Cutter, a detective as sharp and committed to his work as he is wryly hilarious. Gideon Bliss, a Cambridge dropout in love with one of the missing girls, stumbles into a role as Cutter's sidekick. And clever young journalist Octavia Hillingdon sees the case as a chance to tell a story that matters—despite her employer's preference that she stick to a women's society column. As Inspector Cutter peels back the mystery layer by layer, he leads them all, at last, to the secrets that lie hidden at the house on Vesper Sands. By turns smart, surprising, and impossible to put down, The House on Vesper Sands offers a glimpse into the strange undertow of late nineteenth-century London and the secrets we all hold inside us.